Chlorophyll nitrogen isotope values track shifts between cyanobacteria and eukaryotic algae in a natural phytoplankton community in Lake Erie. (February 2019) - Kharbush, Jenan J.; Smith, Derek J.; Powers, McKenzie; Vanderploeg, Henry A.; Fanslow, David; Robinson, Rebecca S.; Dick, Gregory J.; Pearson, Ann
Highlights: Lacustrine range of chlorophyll N isotope fractionation agrees with lab observations. Chlorophyll N isotope fractionation patterns are linked to higher level taxonomy. ε por values become more negative as cyanobacterial abundance increases. ε por can be used to determine the dominant type of phototroph in aquatic ecosystems. Abstract: Chlorophylls are produced by all photosynthetic organisms and are ideal targets for compound-specific isotopic studies of phytoplankton. In laboratory cultures, the difference between the nitrogen (N) isotope ratio (δ 15 N value) of chlorophyll and the δ 15 N value of biomass, known as ε por, varies taxonomically, yielding potential applications for studying productivity in modern and ancient environments. Here we take advantage of the annual cyanobacterial bloom in Lake Erie, USA, to demonstrate ε por patterns in a natural community. The resulting time series shows that environmental observations are similar to laboratory cultures: predicted ε por endmember values range from 4.6‰ to 7.4‰ for eukaryotic algae, and −18‰ to −21‰ for cyanobacteria. Because the range and sensitivity of ε por is similar between laboratory and natural settings, the data support the use of ε por as a reliable tracer of the relative contributions of cyanobacteria and eukaryotic algae to nutrient utilization and primary production in lacustrine environments.